2020
DOI: 10.3390/ma13020415
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Inserts for Enhancing Heat Transfer in PCM Accumulator

Abstract: Phase change materials (PCMs) are applied in heat storage units, as they are able to accumulate the energy in the form of the latent heat of fusion. Thus, they can be used in recovering the excess of heat from various industrial processes. Their main weakness is their low thermal conductivity coefficient, which strongly limits their usage. In this paper, the benefits of the application of metallic inserts in heat storage PCM-based units were elaborated. Two kinds of Al–Si spatial elements (foams and honeycomb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…However, the usage of PCM materials is strongly constrained due to their small thermal conductivity coefficient. To overcome this disadvantage, PCMs having low thermal conductivity coefficients metal inserts are used, which are successfully manufactured by using Investment casting [24]. In a research work using aluminium inserts for enhancing heat transfer in PCM accumulator, two types of metal inserts are successfully manufactured, Al-Si structural elements (foams and honeycomb structures) [24,25].…”
Section: Phase Change Materials Properties: a Metal Casting Perspectivementioning
confidence: 99%
“…However, the usage of PCM materials is strongly constrained due to their small thermal conductivity coefficient. To overcome this disadvantage, PCMs having low thermal conductivity coefficients metal inserts are used, which are successfully manufactured by using Investment casting [24]. In a research work using aluminium inserts for enhancing heat transfer in PCM accumulator, two types of metal inserts are successfully manufactured, Al-Si structural elements (foams and honeycomb structures) [24,25].…”
Section: Phase Change Materials Properties: a Metal Casting Perspectivementioning
confidence: 99%
“…This also provides greater thermal stability as cyclic melting and freezing of the PCM reduces both the range of temperature fluctuations and restricts that fluctuation about its melting point. Most PCM studies have focused on the functionality of PCM laden heat sinks with investigations of different heat sink geometries, orientations, or power levels [1,2,3,4,5,6,7,8], as well as comparative studies comparing different PCM types [9] and evaluating the impact of high thermal conductivity in-serts to enhance heat conduction [10,11]. Although these studies demonstrated extensions in high power operating times before the system overheated, numerous materials and interfaces between the PCM-laden heat sink and heat source prevent their effective use as the heat generation rates increase.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen mainly affects constantly, and in this respect this phenomenon is well-explored, and taken into account during the processes that involve them [1][2][3][5][6][7]. However, aluminum alloys have been increasingly applied in recent decades [8][9][10][11][12][13][14][15]. They are employed in boat and ship designs, in aviation, astronautics, and in automotive industries, as well as in bridge structures and many other applications.…”
Section: Introductionmentioning
confidence: 99%